Correlation between T-Lymphocyte Subsets, Regulatory T Cells, and Hepatic Fibrosis in Patients with Nonalcoholic Fatty Liver. (31st July 2022) - Wang, Xia; Li, Weiqin; Fu, Jiangfeng; Ni, Yaping; Liu, Kaige
Abstract : Objective . The aim of this study is to assess the relationship between T-lymphocyte subsets, regulatory T cells (Treg), and hepatic fibrosis in patients with a nonalcoholic fatty liver disease (NAFLD). Methods . A retrospective analysis was conducted on 64 NAFLD patients (research group) and 73 healthy subjects (control group) in our hospital from January 2020 to December 2021. T-lymphocyte subsets (Th17) and Treg, liver function (alanine aminotransferase (ALT), aspartate aminotransferase (AST)), hepatic fibrosis indexes (type III procollagen (PCIII), type IV collagen (CIV), laminin (LN), hyaluronic acid (HA)), inflammatory factors (high-sensitivity C-reactive protein (hs-CRP), interleukin 6 (IL-6), interleukin-8 (IL-8)), and oxidative stress (OS) response ((superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), malondialdehyde (MDA)) were tested. The relationship between Th17/Treg and the abovementioned indexes in NAFLD patients was analyzed. Results . In comparison to the control group, Th17 and Th17/Treg were higher in the research group (P < 0.05 ). In addition, liver function, liver fibrosis markers, inflammatory factors, and MDA were elevated, while SOD and GSH-PX decreased (P < 0.05 ). Subsequently, NAFLD patients were divided into groups A (Th17/Treg <1.15, n = 33) and B (Th17/Treg ≥1.15, n = 31) based on their median Th17/Treg levels. It was seen that liver injury, hepatic fibrosis, inflammation, and OS in group A were more severe (P < 0.05 ). The Pearson correlation coefficient revealed that Th17/Treg was positively correlated with AST, ALT, PCIII, MDA, and inflammatory factors but negatively correlated with SOD and GSH-PX (P < 0.05 ).